URINARY NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN AND CREATININE SERUM BPH PATIENTS WITH ACUTE URINE RETENTION TO DETECT KIDNEY FUNCTION DISORDERS - Rahayu, Septina; Hardjowijoto, Sunaryo; Djojodimedjo, Tarmono; Soebadi, Mohammad Ayodhia (Indonesian Journal of Urology, 2016)
Objective: The main objective of this study was to determine renal function in patients with Benign Prostate Hyperplasia (BPH) in acute urinary retention period and two weeks after catheter insertion using creatinine serum and urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) biomarker parameters.Materials & Method:This is an observational co-hort study conducted in patients with BPH with acute urinary retention who came to Soetomo General Hospital, Surabaya. All the patients underwent laboratory investigation that were urinary NGAL and creatinine serum, marker of renal function.Result: The mean creatinine serum of 31 samples when retention phase was 1.6 ± 0.9 mg/dL and it decreased after 2 weeks of urinary catheter insertion (1.46 ± 0.89 mg/dL). Mean urinary NGAL level when retention phase was 308.1 ± 244.8 ng/dL, and after 2 weeks after urinary catheter insertion it decreased to 158.5 ± 123.3 ng/dL. There was significant decreasing creatinine serum and urinary NGAL levels in patients with BPH and acute urinary retention in the retention phase 2 weeks after urinary catheter insertion, with p value < 0.006 and < 0.0001, respectively. There was no significant correlation between the duration of retention and urinary retention volume (p>0.05).Conclusion: There was a significant decreasing creatinine serum and urinary NGAL levels in patients with BPH and acute urinary retention in retention phase and two weeks after urinary catheter insertion. There was no significant correlation between the urinary NGAL and creatinine serum and the duration of retention and urinary retention volume.